The Effect of Third Party Financing and Funds on BCA Syariah Bank Profit (2020-2023) - Matondang, Padlan Hamidi; Rahmah, Azizatur; Darma, Satria (AMK : Abdi Masyarakat UIKA, 2025)
The Effect of Financing and Third Party Funds on BCA Syariah Bank's Profit. In the financial report of BCA Syariah Bank for the period 2020-2023. This research was conducted on the financial report of BCA Syariah Bank, the purpose of the study was to determine the effect of Financing on BCA Syariah Bank, the effect of Third Party Funds on BCA Syariah Bank, and to determine the Effect of Financing and Third Party Funds on BCA Syariah Bank's Profit. The method used in this study is quantitative research. To determine the Effect of Financing and Third Party Funds on BCA Syariah Bank's Profit using statistical tests. Statistical tests are classical assumption tests, linear regression, hypothesis tests and also using the SPSS version 25 for windows application to strengthen manual calculations. Based on the results of this study, the Financing variable shows that the t-count value is 4.564> 1.679 and the sig. value. 0.000 < 0.05, and the Third Party Fund variable shows that the t-value is 7.405 > 1.679 and the sig. value is 0.000 < 0.05. Then the F test result is 672.789 with a sig. value of 0.000. Because this value is smaller than 0.05, H0 is rejected, which means that the regression equation obtained is significant. So it can be concluded that Financing and Third Party Funds have a significant effect on BCA Syariah Bank's Profit.